Integrating Data, Driving Solutions: The Minnesota Information Linking for Kids (Minn-LInK) Project - Johnson, Sydney; Hoffmeister, Michael; Piescher, Kristine (International Journal of Population Data Science, 2026)
Child well-being is complex and spans multiple disciplines and systems. The involvement of children with multiple public service systems (e.g., child protection, juvenile justice, public health, education, children’s mental health) necessitates better service coordination and integration to ensure comprehensive service provision and delivery and promote child well-being. Through partnerships with state agencies, the Minnesota Linking Information for Kids (Minn-LInK) project links administrative data from a variety of systems to create a resource for interdisciplinary research regarding vulnerable populations, often focusing on cross-system involved children and families experiencing poverty. Minn-LInK currently houses over 20 years of state-wide individual level administrative data from multiple Minnesota systems, including educational data, child protection and children’s mental health records, data on the receipt of public services such as food assistance or childcare assistance, juvenile justice and adult criminal justice data, and records of incarcerated adults, including sentence and offense information. This presentation will demonstrate how the longitudinal scope of Minn-LInK data allows researchers to consider complex questions about programs and policies that change over time and creates opportunities for ongoing follow-up of large-scale evaluations. We will also outline our plans for future expansion to increase capacity for new research questions, additional users, and greater responsivity to the needs to public systems and practitioners.